Improving the Nutritional Quality of Pregnant Women Through Training in Additional Vegetable Training in Additional Vegetable (Carrot) Food Processing : Peningkatan Kualitas Gizi Ibu Hamil Melalui Pelatihan Pengolahan Makanan Tambahan Berbahan Dasar Sayur (Wortel) (JURNAL UNEJ, 2023)
Balanced nutrition for pregnant women indicates that the food consumption required by pregnant women must meet nutritional requirements for the mother and baby in her womb. This is because during pregnancy nutritional needs are not only intended for the mother but are also needed for the growth and development of the fetus. Therefore, during pregnancy, the nutrition needed by pregnant women is more than when the mother is not pregnant. The method used in this service is in the form of providing training, where before the training activity participants are also given education regarding the importance of nutrition during pregnancy. The results obtained from this activity were an increase in pregnant women's knowledge about the importance of nutrition during pregnancy, namely from 40% to 80%, apart from that, the ability of pregnant women to process vegetables, especially carrots, also increased. The importance of nutrition by utilizing additional food based on local carrot-based food through educational and training activities can increase the knowledge of pregnant women in optimizing nutritional status and preventing complications during pregnancy as well as increasing the skills and independence of pregnant women in processing food ingredients.